Improvement effect of Lycium barbarum polysaccharide on sub-health mice - Zhao, Rui (Iran J Basic Med Sci, 2015)
OBJECTIVE(S): Sub-health has been described as a chronic condition of unexplained deteriorated physiological function, which falls between health and illness. In the present study, we evaluated the effects of Lycium barbarum polysaccharide (LBP), a polysaccharide fraction purified from Lycium barbarum (L. barbarum) on the sub-health mice. MATERIALS AND METHODS: The sub-health model mice were built through compound factors. The mice were given intragastric administration of LBP at low dose (50 mg•kg-1) and high dose (100 mg•kg-1), respectively. After LBP treatment for 4 weeks, the antioxidant ability, enhancing immune function and anti-fatigue activity were detected. RESULTS: The results showed that LBP could enhance antioxidant ability in sub-health mice. LBP could effectively improve immunity of sub-health mice and protect the immune organs, such as thymus. In addition, LBP showed anti-fatigue ability in sub-health mice. CONCLUSION: LBP could improve sub-health state caused from composite factor through three aspects, such as increasing antioxidant ability, promoting T lymphocyte proliferation, inhibiting thymus lymphocyte apoptosis, and alleviating fatigue.